Authentic leadership and resilience as perceived by healthcare providers - Saeed Salem Alghamdi; Bander Ebrahem Jafare; Anwar Hussain Yahia; Abdullah Ahmed Alzahrani; Naïf Abdullah yahya; Mohammed Ali Alqarni; Fayez Awadh Alsulami; Turki Khalid Alshutayri; Ahmed Saleh Al-Shehri; Ahmed Ateg Allah alshutaiyri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background : Most American healthcare organizations are concerned about healthcare reform, poor patient care quality, and leadership shortages (Lee, 2010). Physicians who hold leadership positions often attend leadership seminars, meet with executive coaches, or pursue a master's degree in business administration. Authentic leaders provide a supportive environment that promotes employee autonomy and excitement for work. Employees that feel supported are more likely to engage in proactive behaviors . Aim of the Study :The purpose of this study is to identify the authentic leadership and its relation healthcare provider’s self-efficacy. Method: A descriptive correlational research design was utilized to attain the purpose of this study. Setting: This study was conducted at the King Abdul-Aziz University Hospital. ​The study was carried out in all hospital departments, including critical care units (Adult ICU, CCU, pediatric ICU, neonatal ICU, cardiac catheterization unit, hemodialysis unit, and surgical operating unit), outpatient clinics, and inpatient departments (obstetrics, medical, surgical, pediatric, reception, and emergency departments). Sampling :Convenience sampling was conducted to assigned the participants, the studied subject consist of two groups;seventy -five physicians who work in critical care units and inpatient units/ departments.Group 2 staff nurses outof 335 nurses 200 nurses were assigned Measurement:Two tools were utilized to conduct this research. Authentic Leadership Questionnaire (ALQ) It is aimed to assess authentic leadership levels from the prospectives of healthcare providers The questionnaire includes 16 itemswhich were classified into four dimensions (subscales). General Self-Efficacy Scale (GSES) to assess general self-efficacy levels. It consists of 10 items. Results:the highest total score (72.67 ± 12.32) was observed in the internalized moral perspective dimension that was stated in the first rank among AL dimensions. While the lowest total score (64.67 ± 12.65) was found in the relational transparency that was observed at the last rank among authentic leadership dimensions. that there was a highly statistically significant positive correlation between all dimensions of authentic leadership and healthcare providers’ self-efficacy (rs = 0.594, p<0.001) from the studied subject. Conclusion: The participants perceived their leaders as effective authentic leaders, and they perceived themselves to have a better GSE. there was correlation between authentic leadership and GSE. These results contribute to fostering true leadership skills in nurse managers.